2019
DOI: 10.3390/ijms20143380
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Nobiletin, A Citrus Flavonoid, against Alzheimer’s Disease and Parkinson’s Disease

Abstract: Alzheimer’s disease (AD), which is characterized by the presence of amyloid-β (Aβ) plaques and neurofibrillary tangles, accompanied by neurodegeneration, is the most common form of age-related neurodegenerative disease. Parkinson’s disease (PD) is the second most common neurodegenerative disease after AD, and is characterized by early prominent loss of dopaminergic neurons in the substantia nigra pars compacta. As currently available treatments are not able to significantly alter the progression of these disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
91
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(110 citation statements)
references
References 98 publications
3
91
0
Order By: Relevance
“…Recently, NOB has become a hotspot as one of candidates for the prevention of Alzheimer's disease (AD), which is a chronic and devastating progressive age-associated neurodegenerative disease. Nakajima et al [25] have shown that NOB improved the pathological features of AD. Qi et al [26] reported on the protective effects of NOB on neuroinflammation and cognitive deficits of three-month old mice.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NOB has become a hotspot as one of candidates for the prevention of Alzheimer's disease (AD), which is a chronic and devastating progressive age-associated neurodegenerative disease. Nakajima et al [25] have shown that NOB improved the pathological features of AD. Qi et al [26] reported on the protective effects of NOB on neuroinflammation and cognitive deficits of three-month old mice.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the roles of nobiletin in human health have been investigated extensively, and it was suggested that nobiletin was beneficial to human health through its various activities, such as anti-depressant 25 , anti-allergy 26 , anti-pigmentation of skin 27 , and inhibition of heart failure progression 28 . Currently, the neuroprotective effect of nobiletin has attracted increasing attentions, and nobiletin has been expected to be a potential neuroprotectant for the treatment of cerebral ischemia-reperfusion injury 29 , Alzheimer's disease, and Parkinson's disease 30 . Therefore, the development of functional foods or supplements, which are rich in nobiletin, may be of great importance for human health.…”
mentioning
confidence: 99%
“…Nobiletin (Figure 1), one kind of multimethoxyl flavone extracted from Citrus reticulate, has attracted great attention due to its extensive pharmacological effects, such as antioxidant and anti‐inflammation [16] . A resent research showed nobiletin exhibited activities in neuroprotection against serum withdrawal and hydrogen peroxide‐ induced cytotoxicity through down‐regulating the expression of pro‐apoptotic protein Bax [17] . Another study revealed neuro‐inflammation response could be inhibited by nobiletin through reducing the release of inflammatory mediators [18]…”
Section: Introductionmentioning
confidence: 99%